ISO 50001 : a strategic guide to establishing an energy management system / Alan Field. - Field, Alan (Auditor) (IT Governance Publishing, 2023)
ISO 50001 - A strategic guide to establishing an energy management system provides a practical but strategic overview for leadership teams of what an EnMS (energy management system) is and how implementing one can bring added value to an organisation.